Inside Cover: Rapid Evaluation of Power Degradation in Series Connection of Single Feeding Microsized Microbial Fuel Cells (Energy Technol. 8/2014). Issue 8 (August 2014) - Rojas, Jhonathan Prieto; Alqarni, Wejdan; Hussain, Muhammad Mustafa
<x xml:space="preserve">Abstract</x> Series arrays of Microbial Fuel Cells: MFC technology is an attractive and innovative approach for energy generation by reusing waste resources. Sustainable, membrane‐less, single feeding, microsized microbial fuel cells are fabricated to quickly evaluate the power generation and viability of a series array of three MFCs as described in the Communication authored by Jhonathan Rojas, Wejdan Alqarni, and Muhammad Hussain from King Abdullah University of Science and Technology on page 673. The cover image shows the applied design that generated 45 mW m−3 power. The study shows that the power generation of the series array of microsized MFCs can be strongly limited due to high internal resistance, non‐uniformities in assembly, and the single‐channel feeding system, which could lead to an unwanted voltage reversal effect.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>